Strikingly high fraction of fast rotators in Magellanic Cloud star clusters - Ettorre, Greta; Mazzi, Alessandro; Girardi, Léo; Marigo, Paola; Pastorelli, Giada; Goudfrooij, Paul; Williams, Benjamin F; Bellini, Andrea; Bressan, Alessandro; Chen, Yang; Correnti, Matteo; Costa, Guglielmo; et al. (Monthly notices of the Royal Astronomical Society, 2025)
There has been growing evidence that the rich star clusters in the Magellanic Clouds contain significant fractions of rapidly rotating stars. In this work, we aim to constrain these fractions by studying the colour–magnitude diagrams of four star clusters, selected among those with the most striking signatures of fast rotators. Using isochrones derived from parsec v2.0 stellar tracks, we generate distinct stellar populations, each covering a limited interval of initial rotation rates ⁠, referred to as ‘Partial Models’ (PMs). Using optimization algorithms and Monte Carlo Markov Chains, PMs are combined to create the final best-fitting model. In our analysis, we adopt two key assumptions: a uniform age and an isotropic distribution of stellar spin axes within each cluster. The solutions are allowed to explore the entire range of ⁠, and different values of age, metallicity, distance, and foreground extinction. We find that the rotational velocity distributions in all four clusters reveal a high fraction of stars with close to the break-up value, in all cases. Specifically, the fraction of stars with exceeds 80 per cent in the clusters NGC 419 of the Small Magellanic Cloud (SMC) and NGC 1831 and NGC 1866 of the Large Magellanic Cloud (LMC). For NGC 2203 of the LMC, this fraction is smaller, although it still exceeds 50 per cent, confirming that also this cluster is mainly populated by fast-rotating stars.
Online verfügbar: 10. April 2025, Artikelversion: 01. Mai 2025
Gesehen am 11.11.2025